19th International conference on dependability and quality management ICDQM-2016 (review of the proceedings) - Pokorni, Slavko J. (Vojnotehnički glasnik / Military Technical Courier, 2016)
The article presents the basic information about the overal results, significance, international programme committee and working areas of the 19th DQM International Conference on Dependability and Quality Management ICDQM 2016 and 7th DQM International Conference on Life Cycle Engineering and Management (papers printed in Serbian, English and Russian), which was held under the same acronym ICDQM-2016. The number and structure of papers of both conferences are given in Sections: Military Engineering, Quality Engineering, Reliability Engineering, Industrial Engineering, Systems Engineering, Energy Efficiency and Lean Production. Only the plenary papers presented by the participants from the Armed forces and the Ministry of Defense of the Republic of Serbia are reviewed. This year’s conference has been the best so far regarding the number of papers from pаrticipants from the Armed forces and the Ministry of Defense of the Republic of Serbia.
Keywords: quality; reliability; military engineering; conference; review